2015
DOI: 10.1586/14737140.2015.1038247
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic, predictive and potential surrogate markers in castration-resistant prostate cancer

Abstract: Several novel therapeutic agents have demonstrated improvement of overall survival and further patient relevant endpoints in the setting of castration-resistant prostate cancer. Nevertheless, two questions have become increasingly relevant: are there any prognostic or predictive markers that could ease clinical decision-making using risk stratification and risk-adapted treatment in order to provide a benefit for the patient? Furthermore, against the background of increasing possibilities of therapy sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…GS may have reduced prognostic significance in mCRPC compared with earlier disease, although a higher GS, which might increase during the natural history of the disease, has been associated with shorter OS [1,23]. There are, however, several considerations when analyzing the predictive or prognostic value of GS in clinical trials and routine clinical practice in mCRPC patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GS may have reduced prognostic significance in mCRPC compared with earlier disease, although a higher GS, which might increase during the natural history of the disease, has been associated with shorter OS [1,23]. There are, however, several considerations when analyzing the predictive or prognostic value of GS in clinical trials and routine clinical practice in mCRPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic landscape in metastatic castration-resistant prostate cancer (mCRPC) has expanded in recent years with the introduction of several novel anticancer drugs prolonging overall survival (OS), including the CYP17 inhibitor abiraterone acetate (AA), the androgen-receptor antagonist enzalutamide, the radioisotope alpharadin (radium-223), the taxane cabazitaxel, and the vaccine sipuleucel-T (marketing authorization withdrawn in the European Union) [1][2][3]. These treatment options exploit different mechanisms of action; therefore, different biomarkers and prognostic variables are most relevant to measuring and predicting treatment response for different agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, OS as a measure of therapeutic success becomes less useful as the course and duration of diseases such as cancer move from being acute to more chronic; longitudinal effects of chronic disease such as comorbidities and additional ongoing treatments add further limitations to OS as an outcome. 90,91 As a solution, there has recently been a steady move (by regulatory bodies) away from OS as a clinical end point measure and towards more short-term surrogate measures.…”
Section: Definition and Examples Of Surrogate Outcomesmentioning
confidence: 99%
“…In our cohort of patients, the Gleason score did not correlate significantly with OS. Previous findings are contradictory in this regard; some found that a higher Gleason score is associated with shorter OS,22 23 while others found that a value <8 did not predict a greater benefit 24. The value of the Gleason score is well established in earlier stages of the disease, but its usefulness in mCPRC remains unclear.…”
Section: Discussionmentioning
confidence: 96%